1992
DOI: 10.1161/01.str.23.12.1752
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and correlates of sonographically detected carotid artery disease in the Cardiovascular Health Study. The CHS Collaborative Research Group.

Abstract: on behalf of the CHS Collaborative Research GroupBackground and Purpose: This article describes the prevalence of extracranial carotid atherosclerosis assessed by ultrasonography, its association with risk factors, and its relation to symptomatic coronary disease and stroke in men and women aged >65 years.Methods: Maximum percent stenosis, maximum common carotid artery wall thickness, and maximum internal carotid artery wall thickness were assessed using duplex ultrasound in 5,201 men and women aged >65 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
445
8
31

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 721 publications
(519 citation statements)
references
References 51 publications
35
445
8
31
Order By: Relevance
“…This is supported by a low rate of current smoking, a mean SCORE risk of 3.6%, and a high proportion of diagnosed and treated hypertension at study inclusion. Furthermore, the low prevalence of high‐grade stenosis in our study corresponds with previous studies,4, 15, 16, 27 suggesting a similar rather than a greater atherosclerotic burden. Despite this, our results showed the presence of plaque in 9 of 10 participants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is supported by a low rate of current smoking, a mean SCORE risk of 3.6%, and a high proportion of diagnosed and treated hypertension at study inclusion. Furthermore, the low prevalence of high‐grade stenosis in our study corresponds with previous studies,4, 15, 16, 27 suggesting a similar rather than a greater atherosclerotic burden. Despite this, our results showed the presence of plaque in 9 of 10 participants.…”
Section: Discussionsupporting
confidence: 91%
“…Plaque burden increases with age 15, 16, 17. In previous studies, the prevalence of carotid plaques has varied significantly,3, 18, 19, 20, 21, 22, 23, 24 ranging from 25% to 93%.…”
Section: Discussionmentioning
confidence: 92%
“…33 It is also apparent in our study that SBP is an independent factor influencing CCA-IMT in a multivariate analysis. In light of the result obtained from the study by Rodrigo et al, 34 who have recently shown an inverse relationship between SBP and diastolic blood pressure and antioxidants, including FRAP in hypertensive subjects, (in our study, the correlation coefficient between SBP and FRAP ¼ À0.35, P ¼ 0.005; data not shown), it may be postulated that better antioxidant defence also through decreasing blood pressure levels prevents thickening of the arterial wall.…”
Section: Discussionsupporting
confidence: 58%
“…Increased intima-media thickness (IMT) of the carotid artery is considered to be an index of the progression of atherosclerosis and a useful predictor of a high-risk group of cardiovascular events [10,11,12,13,14,15]. To evaluate whether the drugs named above have potent anti-atherogenic effects on diabetic patients, we did an open randomised prospective study examining the progression of carotid artery IMT as a surrogate end point.…”
Section: Introductionmentioning
confidence: 99%